The association between normal serum sodium levels and bone turnover in patients with type 2 diabetes - Huang, Hai-yan; Huang, Zhi-qi; Hua, Ling-yan; Liu, Wang-shu; Xu, Feng; Ge, Xiao-qin; Lu, Chun-feng; Su, Jian-bin; Wang, Xue-qin (Frontiers in Endocrinology, 2022)
Background: Sodium is a critically important component of bones, and hyponatremia has firmly been established as a risk factor associated with the incidence of fragility fractures. However, researches have also revealed that lower serum sodium are linked to reductions in muscle mass and a higher risk of cardiovascular disease even when these levels are within the normal range. Accordingly, this study was developed to examine the relationships between normal serum sodium concentrations and bone turnover in patients with type 2 diabetes (T2D). Methods: Patients with T2D were enrolled in the present study from January 2021 to April 2022. All patients underwent analyses of serum sodium levels, oral glucose tolerance testing (OGTT), bone turnover markers (BTMs), and dual-energy X-ray absorptiometry (DXA) scanning. BTMs included bone formation markers osteocalcin (OC) and N-terminal propeptide of type-I procollagen (PINP), and bone resorption marker C-terminal telopeptide (CTx). Patients were stratified into three subgroups based on their serum sodium concentrations: low (135.0 – 138.4 mmol/L), medium (138.5 – 141.7 mmol/L), and high (141.8 – 145.0 mmol/L). Results: In total, 372 patients with T2D and sodium levels in the normal range were enrolled in this study. Serum OC and PINP levels were increased from subgroup with the low sodium tertile to that with the high sodium tertile (p for trend < 0.05), whereas CTx level was comparable among the subgroups. A positive correlation was detected between serum sodium levels and both lnOC (r = 0.210, p < 0.001) and lnPINP (r = 0.196, p < 0.001), with these relationships remaining significant even following adjustment for age, sex, body mass index (BMI), and HbA1c. Only after adjusting for these four factors a positive correlation was detected between serum sodium levels and CTx levels (r = 0.108, p < 0.05). Linear regression analyses revealed that following adjustment for potential covariates, serum sodium level was and positively significantly associated with lnOC level (β = 0.134, t = 2.281, p < 0.05) and PINP level (β = 0.179, t = 3.023, p < 0.01). Conclusion: These results highlight a significant association between low-normal serum sodium levels and low bone turnover.